Microalgae as a renewable fuel resource: a comparative study on the thermogravimetric and kinetic behavior of four microalgae. Issue 5 (9th April 2019) - Vuppaladadiyam, Arun K.; Zhao, Ming; Memon, Muhammad Zaki; Soomro, Abdul F.
Abstract : Four different microalgae, Chlorella vulgaris (CV), Spirulina (SP), Chroococcus (CC) and mix culture (MC), were pyrolyzed at heating rates of 10, 15 and 20 °C min −1 up to 800 °C in a thermogravimetric analyzer coupled with a mass spectrometer to investigate their pyrolytic characteristics. Abstract : Four different microalgae, Chlorella vulgaris (CV), Spirulina (SP), Chroococcus (CC) and mix culture (MC), were pyrolyzed at heating rates of 10, 15 and 20 °C min −1 up to 800 °C in a thermogravimetric analyzer coupled with a mass spectrometer to investigate their pyrolytic characteristics. Three stages of devolatilization (dehydration, devolatilization of proteins, carbohydrates and lipids, and decomposition of the solid residue) appeared during the pyrolysis of all the mentioned samples. SP, CV, CC and MC mainly devolatilized in the temperature range 190–464 °C, 170–460 °C, 175–504 °C and 178–504 °C, respectively. Microalgae samples CC and MC were noticed to be thermally more resistant than SP and CV. The iso-conversional methods were used to interpret thermogravimetric data to investigate the kinetic parameters of algal biomass pyrolysis. The kinetic analysis showed that the activation energy ( E α ) varied over the studied conversion range ( α = 0.1–0.8). The most probable reaction mechanisms for four microalgae were identified by using the compensation effect and master plots method. The evolved gas species were quantified by using a semi-quantitative method and found that H2, CO and CO2 were the predominant gas species. Overall, the obtained data of the thermal and kinetic behavior of selected microalgae samples are expected to facilitate the design and optimization of pyrolysis of low-lipid microalgae.